CHALLENGES OF TEACHING PORTUGUESE IN MULTILINGUAL CONTEXT IN MOZAMBIQUE - Alexandre António Timbane (Travessias, 2014)
The development of any country is closely linked to the formation of human resources. The education is important because it provides professionals for different areas of social life. In turn, the quality of trained staff is a result of the good work done by teachers. Hence arises the question: will the Mozambican teachers are prepared to deal with the teaching of writing and the variety of the Portuguese of Mozambique? This paper deals with the complexity of the training of Mozambican teachers, in which I will present the organization of teaching, examine the methods of teaching portuguese and finally discuss ways to improve teacher training aimed at improving the quality of education. From experience it is concluded that there is need for investment in qualitative teacher training and materials for the teachers work is increasingly efficient means. Is necessary to review the methodology of teaching the Portuguese including the teaching of writing because the school teach the writing without teaching what is writing (CAGLIARI, 2009a, p.83). We must prioritize local curriculum in which prioritizes the cultural experience of the child. Should provoke reflection on language is fleeing mechanical activities that do not help the student, relying on a sociolinguistic reeducation that values linguistic diversity and variety of the portuguese in Mozambique, because according Bagno (2008 ) nothing in the language is by chance.